Web Extensions for Semantic Data Creation - Jovanovik, Milos; Trajanov, Dimitar; Markovski, Adam (Faculty of Computer Science & Engineering, Skopje, 2012)
The existence of the Semantic Web is very dependent on the semantic content which exists on the current web. Thus, the process of creating more semantic content actually means building the Semantic Web itself. This process can be done using various information extraction and annotation mechanisms. However, they usually focus on domain specific approaches manually built and adapted for pre-assigned tasks, and are designed for more advanced users. In this paper we introduce an innovative way for creating semantic data and content by involving the common web user and with the use of an easily operated extension for content bookmarking, supported by a blogging platform. The content gathered by the user is processed by existing service-oriented information extractors where it is semantically annotated, and then published on the web.